2017
DOI: 10.1038/emm.2017.125
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced ER stress and inflammation are mediated through C/EBP–DDIT3 signaling in human bronchial epithelial cells

Abstract: Cadmium (Cd), a major component of cigarette smoke, disrupts the normal functions of airway cells and can lead to the development of various pulmonary diseases such as chronic obstructive pulmonary disease (COPD). However, the molecular mechanisms involved in Cd-induced pulmonary diseases are poorly understood. Here, we identified a cluster of genes that are altered in response to Cd exposure in human bronchial epithelial cells (BEAS-2B) and demonstrated that Cd-induced ER stress and inflammation are mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Some studies attributed the increase in oxidative stress due to the production of free radicals as well as the induction of inflammation as a possible mechanism of cadmium in causing cellular damage as well as induction of cancer (Liu et al, 2011;Kim et al, 2017). Given the pathological effects of cadmium on renal cancer induction (kun Song et al, 2015) as well as the pivotal role of KLLN and PKHD1 genes in the incidence of kidney disease, in the present study, for the first time, the effect of crocin on the expression of PKHD1 and KLLN genes in renal tissue of male rats were tested for cadmium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies attributed the increase in oxidative stress due to the production of free radicals as well as the induction of inflammation as a possible mechanism of cadmium in causing cellular damage as well as induction of cancer (Liu et al, 2011;Kim et al, 2017). Given the pathological effects of cadmium on renal cancer induction (kun Song et al, 2015) as well as the pivotal role of KLLN and PKHD1 genes in the incidence of kidney disease, in the present study, for the first time, the effect of crocin on the expression of PKHD1 and KLLN genes in renal tissue of male rats were tested for cadmium.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified the kidney as the most common organ involved with this element (Sá et al, 2016). Effect on message transmission (Thévenod., 2009), peroxidation of unsaturated fatty acids, inhibition of DNA repair system, inhibition of DNA methylation (Hartwig & Schwerdtle, 2002), depletion of antioxidants, dysfunction of E-cadherin protein, interaction with different ions, oxidative stress induced by free radicals overproduction (ROS) (Liu et al, 2011), inflammation and subsequent DNA oxidation, decreased levels of antioxidants, apoptosis disorder and increased activity of some proteases are potential mechanisms of toxic effects of cadmium on tissue damage (Kim et al, 2017;Mahdavi et al, 2011). Therefore, cadmium has been proposed as a candidate for alteration in the expression of effective genes resulting from kidney cancer (Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium chloride, 0.1 M ER stress, unfolded protein response [27][28][29][30][31] Magnesium chloride, 0.1 M (as a divalent metal salt)…”
Section: Drosophila Strains and Treatmentsmentioning
confidence: 99%
“…BEAS-2B and NHBE cells were seeded at a density of 2.0×10 5 cells per well in 6-well plates and incubated until they reach 70-80% confluency. Cells were then transfected with miR-181a-2-3p mimics and/or inhibitors, followed by treatment with or without Cd for 24 h (27,28).…”
Section: Treatmentmentioning
confidence: 99%
“…Cd, a major component of cigarette smoke and particulate matter, induces inflammatory responses and endoplasmic reticulum stress in human bronchial epithelial cells via the C/EBP-DDIT3 signaling pathway (28). Thus, we investigated whether expression of miRNAs is influenced by Cd treatment in BEAS-2B and NHBE cells.…”
Section: Mir-181a-2-3p Is Downregulated In Lung Tissues and Serum Of mentioning
confidence: 99%